GP79 Is it a port-wine stain?: vascular birthmark on the face posing a diagnostic challenge. (June 2019) - Sazali, Hafsah; Browne, Fiona; Dvorakova, Veronika; Murphy, Annette; Allen, Nicholas
Abstract : Infantile haemangioma is a group of vascular tumours arising during infancy which has characteristic clinical and histological findings. Although this type of tumours has a typical presentation, they can mimic the appearance of other vascular lesions. Two infants, 2 weeks and 5 weeks of age respectively were referred to the dermatology department for 'port-wine stain' as well as 'orbital cellulitis' and also considered as possible 'Sturge Weber Syndrome'. Both infants had vascular lesions in V1 distribution of the trigeminal nerve noticed at birth and in the days prior to presentation developed significant swelling of the affected eyelid. Clinically these are telangiectatic macular lesions present on the eyelid and forehead, extending to the scalp, neck, shoulder and chest in one infant and affecting the perioral area and lower lip with ulceration in the other infant. In both infants there was a significant swelling of the upper eyelid involved resulting in complete closure of the eye. Magnetic Resonance Imaging and Angiography demonstrated intraorbital haemangioma together with abnormalities within the arterial system. One of the infants had involvement of the intracranial arteries and aortic arch qualifying for PHACES syndrome, and the other had involvement of the soft palate. Both patients were commenced on oral propanolol resulting in rapid shrinkage of the eyelid haemangioma, progressive healing of the lip ulceration and regression of the cutaneous component of the haemangioma. Treatment was well tolerated and is expected to continue for 6 to 12 months. In summary these are two cases of segmental infantile haemangioma with involvement of internal structure mimicking capillary malformation associated with Sturge Weber Syndrome. These cases demonstrate the importance of distinguishing between infantile haemangioma and other vascular lesions to ensure early commencement of appropriate treatment as well as identification and management of internal involvement.